What influences safety in paramedicine? Understanding the impact of stress and fatigue on safety outcomes. Issue 4 (15th June 2020) - Donnelly, Elizabeth A.; Bradford, Paul; Davis, Matthew; Hedges, Cathie; Socha, Doug; Morassutti, Peter; Pichika, Sathish Chandra
Abstract: Objective: The purpose of this study was to build on extant research linking fatigue to safety outcomes in paramedicine by assessing the influence of a multiplicity of workplace stressors, including chronic and critical incident stresses on safety outcomes. Methods: A cross‐sectional survey was deployed to 10 paramedic services in Ontario. Validated survey instruments measured operational and organizational chronic stress, critical incident stress, post‐traumatic stress symptomatology (PTSS), fatigue, safety outcomes, and demographics. Analysis of covariance assessed associations of workplace stresses with safety outcomes and corroborated findings using hierarchical linear model and generalized estimating equations (GEE) by taking into account paramedic service when assessing the proposed associations. A non‐responder survey was conducted to asses for demographic differences in those who did and did not complete the survey. Results: This survey had a response rate of 40.5% (n = 717/1767); 80% of paramedics reported an injury or exposure to pathogen, 95% reported safety compromising behaviors, and 76% reported medical errors. In the GEE analyses, paramedic injury was significantly related to fatigue (0.13, SE = 0.06, P = 0.020), critical incident stress (0.03, SE = 0.01, P < 0.01), and PTSS (0.03, SE = 0.01, P < 0.01). Safety compromising behaviors were significantly associated with fatigue (0.37, SE = 0.06, P < 0.01), organizational stress (0.06, SE = 0.01, P < 0.01), and critical incident stress (0.01. SE = 0.01, P = 0.017). Medication errors were significantly related to fatigue (0.12, SE = 0.05, P < 0.01). Finally, the bivariate analysis showed increased stress factors and fatigue was associated with increased safety outcomes. Conclusion: These findings illustrate that a host of different stressors may influence safety‐related behaviors. For those interested in safety, these findings point to the need for a holistic focus on fatigue and stress in paramedicine.